Student and parent factors as determinants of sexual risk-taking behaviour among gifted adolescents in Ibadan, Oyo State, Nigeria (2014)
The study investigated how student and parent factors could determine sexual risk-taking behaviour among gifted adolescents in Ibadan. The emerging sexuality that accompanies adolescence poses fundamental challenges for young people. The study adopted a descriptive survey research design. Purposive sampling technique was used to select a total number of one hundred and twenty gifted adolescents out of those identified to be gifted in ten Senior Secondary Schools that were randomly picked in Ibadan. Data were analysed using t-test. The result of the first hypothesis revealed that the calculated value t-cal of 2.765 is greater than the table value t-tab of1.966 at 0.05 level of significances with degree of freedom of 198. This implies that there is a significant difference in the sexual risk- taking behaviour of male and female gifted adolescents. The findings of the second hypothesis revealed that the mean score of 2.2570 was recorded for gifted adolescents whose parents have low educational attainment while 1.8900 was recorded for those whose parents are highly educated. The implication of this is that there is a significant difference in the sexual risk- taking behavior of gifted adolescents based on their parents' educational attainment. Based on these findings, il was recommended that public enlightenment must be given on sex education because majority of our people still believe that it is a taboo to expose young children to sex education.